COMPETITIVE PERSONNEL TRAINING SYSTEM IN DEVELOPED COUNTRIES - Jo‘rayev Soxibjon Nodirbek o‘g‘li (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article analyzes the structure of the higher education system of developed countries such as Germany, Japan, South Korea and the USA. Features of management of higher education institutions by the ministry and local governments are described. Positive trends such as higher education policies of developed countries and protection of the interests of higher education institutions by the government have been revealed. Measures taken by developed countries to solve problems in higher education are analyzed. Strategic planning and coordination directions of activities of higher education institutions have been researched in order to use available funds rationally and efficiently. Issues of improving relations between the state and higher education institutions are described in the directions of higher education reform. A scientific conclusion and practical recommendations related to the training of competitive personnel in the higher education system are given.